2011
DOI: 10.1111/j.1470-6431.2011.01020.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing the evidence base of patient and public involvement in health and social care research: the case for measuring impact

Abstract: While patient and public involvement (PPI) in health and social care research has progressed successfully in the last decade, a range of difficulties with the evidence base exist, including poor understanding of the concept of impact, limited theorization and an absence of quantitative impact measurement. In this paper, we argue that a paradigm change towards robust measurement of the impact of involvement in research is needed to complement qualitative explorations. We argue that service users should be colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(157 citation statements)
references
References 26 publications
3
154
0
Order By: Relevance
“…The case for evaluating PPI impact draws upon the methodological case for the need to know what is working and what does not work well in PPI, 198 and the economic case, as PPI is relatively resource-intensive. 30 However, our survey and scoping, and previous systematic and structured reviews of PPI in research, showed that there is little recording of PPI activity and costs in publicly accessible research study information, and in published papers. 19,29 Our analysis of the case studies clearly showed that outcomes of PPI were far easier to identify than the mechanisms and context that led to them.…”
Section: Impact and Outcomes Of Patient And Public Involvementmentioning
confidence: 84%
See 3 more Smart Citations
“…The case for evaluating PPI impact draws upon the methodological case for the need to know what is working and what does not work well in PPI, 198 and the economic case, as PPI is relatively resource-intensive. 30 However, our survey and scoping, and previous systematic and structured reviews of PPI in research, showed that there is little recording of PPI activity and costs in publicly accessible research study information, and in published papers. 19,29 Our analysis of the case studies clearly showed that outcomes of PPI were far easier to identify than the mechanisms and context that led to them.…”
Section: Impact and Outcomes Of Patient And Public Involvementmentioning
confidence: 84%
“…Finally, concerns raised elsewhere that there is little systematic evaluation of PPI by researchers in their studies 21,30 were also highlighted in the RAPPORT study findings. Research teams that are already fully engaged with PPI and well resourced in terms of PPI staff and time are likely to work towards systematic evaluation of impact, for example as suggested by the PiiAF project.…”
Section: Key Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is further enhanced by the cultural awareness PPI offers, the potential for improving research design and data collection tools and the identification of areas of inquiry that might otherwise be overlooked. Staniszewaska et al (2011) add that further impact could be achieved by PPI in research by joint working on developing ways to measure impact.…”
Section: Patient Empowerment and Ppi Impactmentioning
confidence: 99%